Scientific method for ecological research - Ford, E. D. (Edward David) (Cambridge University Press, 2000)
"Scientists tend to take the thought processes that drive their research for granted, often learning them indirectly by observing first their supervisors and then their colleagues. This book emphasizes the advantages of being explicit about these thought processes and aims to help those undertaking ecological research to develop a critical attitude to approaching a scientific problem and constructing a procedure for assessment. The outcome is a text that provides a framework for understanding methodological issues and assists with the effective definition and planning of research. As such, it represents a resource for anyone embarking on their research career. It also provides a source of information for those more experienced researchers who are seeking to strengthen the methodology underlying their studies or who have an interest in the analysis of research methods in ecology."--Jacket